Biliary-Enteric Drainage vs Primary Liver Transplant as Initial Treatment for Children With Biliary Atresia - LeeVan, Elyse (JAMA Surg, 2018)
IMPORTANCE: Some infants with biliary atresia are treated with primary liver transplant (pLT), but most are initially treated with biliary-enteric drainage (BED) with a subsequent salvage liver transplant. Given the improvements in liver transplant outcomes, it is important to determine whether BED treatment remains the optimal surgical algorithm for patients with biliary atresia. OBJECTIVE: To compare the survival of patients with biliary atresia initially treated with BED with patients who underwent pLT. DESIGN, SETTING, AND PARTICIPANTS: This cohort study used deidentified records from the California Office of Statewide Health Planning and Development database to identify patients with biliary atresia (n = 1252) between January 1, 1990, through December 31, 2015. Patients were categorized into 1 of 2 cohorts: those who received BED treatment and those who underwent pLT. Excluded from the study were those born before January 1, 1995, and those without any documented operative intervention by age 5 years. Data analysis was performed from January 1, 1990, to December 31, 2015. MAIN OUTCOMES AND MEASURES: Overall survival was compared between the BED and pLT cohorts using the Kaplan-Meier method. The treatment’s association with treatment era was examined by comparing survival before 2002 and on or after January 1, 2002. RESULTS: In total, 1252 patients with biliary atresia were identified. After exclusions, 626 remained; of these patients, 351 (56.1%) were female and 275 (43.9%) were male with a median (interquartile range) age at intervention for initial BED treatment of 65 (48-81) days. Among the 626 patients studied, initial BED treatment was performed in 313 patients (50.0%), and pLT was performed in 313 patients (50.0%). Although patients who underwent pLT had a higher mortality rate within the first 3 months after the procedure, they had a reduced risk of long-term mortality compared with patients initially managed with BED treatment (hazard ratio [HR] ≥6 months after the initial procedure, 0.19; 95% CI, 0.08-0.42; P = .01). Patients requiring salvage liver transplant had a substantially higher risk of mortality than patients who received pLT (HR, 0.43; 95% CI 0.25-0.76; P = .003). Those who underwent pLT had superior survival compared with BED treatment recipients on or after 2002 (HR, 0.16; 95% CI, 0.05-0.54; P < .001), and that persisted when censoring patients who underwent salvage liver transplant (HR, 0.23; 95% CI, 0.07-0.82; P = .01). CONCLUSIONS AND RELEVANCE: Patients who underwent pLT experienced superior long-term survival compared with patients who underwent BED treatment. Multi-institutional trials are needed to determine which initial treatment is most advantageous to patients with biliary atresia.